Penggunaan Partikel Modal (语气助词) dalam Media Sosial China: Studi Kasus pada Aplikasi Xiaohongshu（小红书） - Yang Nadia Miranti; Maria Chezia - (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2026)
Modal particles in Mandarin Chinese serve a crucial role in conveying meaning and interpersonal nuances in communication. Nonetheless, scholarly investigations into the pragmatic functions of the particles 啊 (a), 吧 (ba), and 呢 (ne) within social media discourse remain scarce. This study aims to elucidate the functions of these modal particles in informal interactions among Mandarin speakers, with particular emphasis on politeness strategies. Data were sourced from speech act excerpts on the social media platform Xiaohongshu (小红书), collected through purposive sampling based on relevant keyword searches. Employing a qualitative methodology grounded in pragmatic theory, the analysis focused on utterance context, speaker intent, and interlocutor responses. Findings reveal that these modal particles play a pivotal role in modulating conversational tone, mitigating illocutionary force, and fostering interpersonal closeness. The study underscores an observable adaptation of modal particle usage in digital communication environments and advocates for further research into politeness mechanisms within online interactions.